(untitled) (Nexo Revista Científica, 2020)
The current study aims to design and explain a comprehensive model for employee productivity improvement indicators. This research is objectively a fundamental-practical study, naturally a survey research, and paradigmatically an exploratory blended research. The statistical population consists of human resource experts and organizational behavior in the qualitative section. The targeted sampling and snowball were used to identify the experts. Twenty experts were employed due to the data adequacy. To test the model, 245 employees of Agriculture Jihad Organization of Ilam province were used. The analysis method included the grounded theory and the structural equation approach. Data were collected through deep interviews along with a 69 item questionnaire. The grounded results indicate the fact that the supportive atmosphere and attention to the learning organization were identified in causal conditions. The main phenomenon of individual characteristics was identified in relation to the intervention conditions, the internal and external factors of the organization. The governing body of organizational culture and laws and regulations and merit-based leaders and human resources skills have been identified in relation to the main strategy of human resource management (HRM) practices. The main consequence of this model is also the productivity of human resources, and the results of the partial least squares model were approved and its relationships were correctly designed.